Advances in graphene-based polymer composites with high thermal conductivity. (24th July 2018) - Chen, Yapeng; Gao, Jingyao; Yan, Qingwei; Hou, Xiao; Shu, Shengcheng; Wu, Mingliang; Jiang, Nan; Li, Xinming; Xu, Jian-Bin; Lin, Cheng-Te; Yu, Jinhong
Abstract : Owing to its excellent thermal and mechanical properties of graphene, graphene-based composites have attracted tremendous research interest in recent years. In particular, graphene with high thermal conductivity becomes an important and promising filler in composites for thermal management. This critical review focus on the recent advances in graphene-based composites with high thermal conductivity. After the introduction of thermal conductive mechanisms of graphene-based composites, the fabrication methods of graphene-based composites are summarized. Then we also discuss currently researches of various graphene-based composites such as graphene/thermoplastic composites and graphene/thermoset composites. Herein, the mechanisms, preparation, and properties of graphene-based composites are discussed along with detailed examples from the scientific literature and the guidance are provided on the fabrication of composites with high thermal conductivity.